1982
DOI: 10.1113/jphysiol.1982.sp014373
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of cat fusimotor endings and their relationship to foci of sarcomere convergence in intrafusal fibres

Abstract: 4. The muscle membrane beneath both ma and mb plates was smooth, or had a few wide, shallow folds; me plates usually had wide, shallow subjunctional folds; numerous deep, narrow folds were characteristic of the md plate. The length of unmyelinated pre-terminal axon or the number of sole plate nuclei were not useful diagnostic features.5. Obvious foci of sarcomere convergence in the capsular sleeve region of dynamic bag1 and static bag2 fibres coincided with the location of motor plates. Additional contraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 29 publications
(39 reference statements)
2
42
0
Order By: Relevance
“…This is not contradicted by any example from the present experiments and is further supported by the similarity between the proportion of driving-category effects (overall 28 % of static responses due to y-stimulation) and the proportion of chain-selective, presumed static y-axonal branches found in spindles in this study and several others (C883 30 %; overall 35 %; Barker, Emonet-Denand, Laporte, Proske & Stacey, 1973;Banks et al 1981;Arbuthnott et al 1982;Kucera, 1985;R. W. Banks, unpublished observations).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This is not contradicted by any example from the present experiments and is further supported by the similarity between the proportion of driving-category effects (overall 28 % of static responses due to y-stimulation) and the proportion of chain-selective, presumed static y-axonal branches found in spindles in this study and several others (C883 30 %; overall 35 %; Barker, Emonet-Denand, Laporte, Proske & Stacey, 1973;Banks et al 1981;Arbuthnott et al 1982;Kucera, 1985;R. W. Banks, unpublished observations).…”
Section: Discussionsupporting
confidence: 63%
“…Fusimotor axons are usually branched intrafusally, but each axon commonly supplies only one type of intrafusal fibre in individual spindle poles, as shown by reconstructions from serial sections carried out independently in three laboratories (Banks, 1981;Banks, Barker & Stacey, 1981; Arbuthnott, Ballard, Boyd, Gladden & Sutherland, 1982;Kucera, 1985). Kucera (1985) reported a higher proportion of axons that were distributed exclusively to a single type of muscle fibre than did the other two groups; nevertheless all three found that a small proportion (3-4%) supplied both the bag, and one chain fibre, usually MS 9016 the longest, whereas a much larger proportion (up to 29 %) supplied the bag2 and at least one chain fibre.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axon terminals of ma plates lie superficial to chain fibres at all levels of section through the plate, whereas m, plates have a pronounced sole plate and sections through the centre of such plates reveal axon terminals indented between finger-like protrusions of muscle sarcoplasm. Individual static y-axons end in either ma plates or m, plates but never in a mixture of the two (Arbuthnott, Ballard, Boyd, Gladden & Sutherland, 1982;Sutherland, Arbuthnott, Boyd & Gladden, 1985).…”
Section: Review)mentioning
confidence: 99%
“…As the gradient in 5mm stretch is different from the gradient of 3mm stretch ( Fig.1), the second gradient of PSD between 15Hz and 35Hz changes when the muscle length changes and when intrafusal fibers are stimulated electrically. It implies the second gradient shows how much intrafusal muscle fibers are activated, probably in the static type of intrafusal muscle fibers like static nuclear chain fibers and a static nuclear bag fiber [9], [10].…”
Section: The Second Gradient Between 15hz and 35hz In Psd;mentioning
confidence: 99%